2012
DOI: 10.1371/journal.pone.0047398
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Human Coding Mutations Affecting Skin Pigmentation Using Zebrafish

Abstract: A major challenge in personalized medicine is the lack of a standard way to define the functional significance of the numerous nonsynonymous, single nucleotide coding variants that are present in each human individual. To begin to address this problem, we have used pigmentation as a model polygenic trait, three common human polymorphisms thought to influence pigmentation, and the zebrafish as a model system. The approach is based on the rescue of embryonic zebrafish mutant phenotypes by “humanized” zebrafish o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…Functional assays for this mutation have not been performed yet, but our results suggest that it could be a cis-acting mutation that may regulate the expression of the gene and contribute to the effect of the SNP L374F. We also acknowledge, however, that this association could be due to the fact that it is in linkage disequilibrium with L374F, whose functional impact has already been described [37]. Further functional work should be done in order to ascertain the significance of this SNP in relation to pigmentation variability.…”
Section: Discussionmentioning
confidence: 77%
“…Functional assays for this mutation have not been performed yet, but our results suggest that it could be a cis-acting mutation that may regulate the expression of the gene and contribute to the effect of the SNP L374F. We also acknowledge, however, that this association could be due to the fact that it is in linkage disequilibrium with L374F, whose functional impact has already been described [37]. Further functional work should be done in order to ascertain the significance of this SNP in relation to pigmentation variability.…”
Section: Discussionmentioning
confidence: 77%
“…We first confirmed that the cyp27c1 transcript is significantly increased in TH-treated zebrafish RPE and dorsal bullfrog RPE by quantitative real-time PCR (Figure 2C). We then determined the cellular expression pattern of cyp27c1 , by performing in situ hybridization on eyes from TH-treated albino zebrafish and vehicle controls [26]. The albino strain was used to improve visualization of staining in the RPE, and we confirmed that it undergoes a TH-dependent switch to vitamin A 2 similar to wild-type strains (data not shown).…”
Section: Resultsmentioning
confidence: 90%
“…Knockdown of the zebrafish orthologues tyr (TYR), oca21p (OCA2), tyrp1a and tyrp1b simultaneously (TYRP1), slc45a2 (SLC45A2), slc24a5 (SLC24A5), or c10orf11 (C10ORF11) lead to a reduction or complete absence of melanin in the eye, with varying responses to visual testing immediately after light exposure, phenocopying the varying degrees of hypopigmentation of the eyes of OCA patients and exemplifying the use of zebrafish to model human pathologies of the eye. [65][66][67][68][69] Multiple zebrafish mutants have been identified with visual defects secondary to functional deficits in the RPE. The vps39 mutant carries a mutation in the zebrafish orthologue of VPS39, a gene encoding a component of the vacuole protein sorting (HOPS) membrane-tethering complex, which coordinates vesicle fusion and transport.…”
Section: Ocular Albinism and Associated Syndromesmentioning
confidence: 99%